2014
DOI: 10.7600/jspfsm.63.189
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for shoulder injuries with or without past history in collegiate rugby players

Abstract: To examine risk factors for shoulder injuries with or without history of the injuries using the stratification analysis for collegiate rugby players. 71 elite rugby players from one university rugby club joined in the preseason medical screening related to their shoulder joints, including basic demographics, history of injuries, and physical findings at that time. Subsequently, the occurrence of shoulder injuries was recorded during four playing seasons. Analysis was stratified with or without history of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Three of the 23 articles targeted study populations within multiple sports settings 28 31 50 , five within the rugby union 38 39 40 42 43 , four within football 25 35 36 37 , three within American football 23 46 47 , three within basketball 24 34 49 , one within lacrosse 32 , one within badminton 26 , one within baseball 48 , one within handball 33 , and one within swimming 27 . Only one of the 23 studies recorded data on professional athletes 35 , whereas the remaining studies focus on non-professional athletes (university athletes: n=17, high school athletes: n=1, junior high school athletes: n=1, elementary school athletes: n=2, and athletes ranging from junior high school to university level: n=1) 23 24 25 26 27 28 31 32 33 34 36 37 38 39 40 42 43 46 47 48 49 50 . Seven articles included data for both male and female athletes 24 26 28 31 33 49 50 , 10 described data regarding only male athletes 23 35 38 39 40 42 43 46 47…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three of the 23 articles targeted study populations within multiple sports settings 28 31 50 , five within the rugby union 38 39 40 42 43 , four within football 25 35 36 37 , three within American football 23 46 47 , three within basketball 24 34 49 , one within lacrosse 32 , one within badminton 26 , one within baseball 48 , one within handball 33 , and one within swimming 27 . Only one of the 23 studies recorded data on professional athletes 35 , whereas the remaining studies focus on non-professional athletes (university athletes: n=17, high school athletes: n=1, junior high school athletes: n=1, elementary school athletes: n=2, and athletes ranging from junior high school to university level: n=1) 23 24 25 26 27 28 31 32 33 34 36 37 38 39 40 42 43 46 47 48 49 50 . Seven articles included data for both male and female athletes 24 26 28 31 33 49 50 , 10 described data regarding only male athletes 23 35 38 39 40 42 43 46 47…”
Section: Resultsmentioning
confidence: 99%
“…Forty-four articles did not describe any sports ISSs or ISGs, one did not report sports injury data, three had retrospective study designs, 11 described surveillance systems that had ceased operation or were not ongoing, and seven presented duplicated information. The search process identified 28 studies, including six English articles 23 24 25 26 27 28 and 22 Japanese articles 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 , that met the inclusion criteria. A flow diagram of the screening and selection process of the studies is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations